Kriterij za izbor odabranih dvoparametarskih modela - Marijana Gjumbir; Tomislav Šikić (Promet - Traffic&Transportation, 1970)
The authors set forth the criterion (i.e. the standard) which makes it possible to select one out of nine two-parameter models, i. e. empiric equations. This refers us to the very simple models which are rather frequently used in different applications including all aspects of traffic. Their utilization has been illustrated by examples.